Liberdade de expressão em períodos eleitorais brasileiros: perspectivas a partir das decisões do Supremo Tribunal Federal e do Tribunal Superior Eleitoral. - Lima Neto, José Guerra de Andrade (2022)
The present work presents research on judgments handed down by the Federal Supreme Court and the Superior Electoral Court, related to freedom of expression and electoral period. It is interesting to say that the electoral period is very important for the preservation and improvement of democracy. This moment in the country's political life needs to understand the necessary regulation regarding the financing and electoral propaganda system, as well as the content and interregnum that electoral campaigns can be carried out. Therefore, this work sought to answer the following question: what are the jurisprudential specifics of the legal-constitutional regime of freedom of expression in electoral periods from the understanding of the Federal Supreme Court and the Superior Electoral Court? In this way, this research was guided by bibliographic reviews and research on the websites of the respective courts, having as a temporal cut the promulgation of the Constitution of the Federative Republic of Brazil of 1988. And as a material cut the use of decisions handed down by the Courts, in their complete formation, that is, the decisions of the Plenary. Search terms and indexers established in the research sites that were correlated to the theme “freedom of expression” were used, such as “thought, “religious, humor, “satire” and “hate”. During the research, there was the observation of a new search term/indexer, namely “magic” for the formation of what will be analyzed as “magic words” when judged in extemporaneous electoral propaganda. As a result, it was found that the appointed courts have a greater regulatory performance when faced with freedom of expression and everything that surrounds this matter in an electoral period, especially with positions that show greater caution regarding the limits of action of candidates and pre-candidates, political parties, coalitions, militancy and party federations. In addition, the issue of campaign financing in Brazil was addressed as a point of freedom of expression for those who can make donations to specific candidates and parties, as a way to demonstrate an opinion that deserves to be victorious in the elections, and thus demonstrate that they are contributing legally. for a better propagation of government ideas and platforms. With the aim of presenting another way of financing electoral campaigns, and not intending to make comparisons, it was briefly stated how the United States of America carries out this fundamental question for freedom of expression and opinion on political platforms and of government. In the end, this work demonstrates that there are clear legal and jurisprudential guidelines for the Brazilian electoral period to be equitable and within an appropriate regulation forecast for this unique moment in democracy.